Challenges of Blood Transfusions in β-Thalassemia during COVID-19 Pandemic in Low Middle-Income Country - Kashif Ali; Kashif Rizvi; Saqib Hussain Ansari; Faisal Zahid (Research Center for Rational Use of Drugs (RCRUD), 2022)
In China Hubei province, Wuhan was recognized as the focus of an epidemic of pneumonia of unidentified origin in December 2019. Ultimately, intense focus on the disease was raised worldwide and in China. as a result, on January 7, 2020, Chinese research scientists identified the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in an affected patient in Wuhan. Beta thalassemia is a congenital hereditary disorder of inefficient erythropoiesis that leads to peripheral red cell breakdown due to defective β-globin series. The severity of the disease depends on multiple genetic and environmental factors. Individuals with beta-thalassemia are classified based on their transfusion demands as having transfusion-dependent thalassemia (TDT) or non-transfusion-dependent thalassemia (NTDT). Routine transfusion remains the recommended standard management for beta-thalassemia, as it efficiently controls the thalassemia symptoms. If left untreated, Beta thalassemia major (BTM) can eventually induce spleen enlargement, deformation of bone because of bone marrow growth, and heart failure as a result of severe anemia.3, 4, 5, 6